Historical interpretation in law: content and types - I. A. Minnikes; I. V. Minnikes (Правоприменение)
The subject of the study is historical method of interpretation in law, its capacities and types. Despite the recognition of historical interpretation by legal science, there are no specialized works and there is no consensus on the content of this method of interpretation. Historical interpretation is considered both as an interpretation based on a previous rule of law, as an interpretation considering the conditions for the adoption of the norm, and as an interpretation based on the practice of applying the interpreted norm.The purpose of the study is to substantiate the authors' hypothesis that historical interpretation in law is an intellectual activity that involves clarifying the content of a legal prescription, achieved based on identifying legal and non-legal factors that both precede the creation of the norm and accompany its adoption. In addition, the authors set the task to identify those factors that should be taken into account in historical interpretation, as well as to classify the types of historical interpretation. The analysis of historical interpretation is made using scientific methods: induction and deduction, formal legal, comparative legal synchronous and diachronic methods.The main results, scope of application. Historical interpretation considers political, economic, social, and legal factors. Legal factors include the rules of law that preceded the interpreted norm, repealed acts, official and unofficial documents of law-making entities, draft laws, acts and the norms contained therein that accompanied the interpreted regulation, i.e. were adopted simultaneously with the interpreted norm, as well as other factors, such as the level of development of legal science and legal technique.The authors suppose that historical interpretation cannot be considered as a homogeneous way of interpretation. In reality, the historical interpretation in law can be carried out using different techniques and methods, in relation to heterogeneous legal prescriptions, and carried out by subjects with different legal status. Therefore, several grounds for classifyinghistorical interpretation are proposed. First, it is a classification that considers the connection of historical interpretation with the other ways of interpretation. According to this criterion, it is possible to divide it into a proper historical and a complex historical interpretation. Complex historical interpretation includes historical-systematic, historical-functional, historical-teleological, historical-legal, and historical-linguistic interpretation. Second, the basis may be the sources of law that contain the rules of law. On this basis, historical interpretation is divided into the interpretation of prescriptions of normative legal acts, legal customs, normative contracts, etc. Third, it is possible to classify the historical interpretation, depending on whether the rule of law is valid or not, into the historical interpretation of the rules that have lost their legal force and the historical interpretation of the rules of the current law. The latter, in its turn, is divided into the interpretation of the current legal norms of the current content and those legal norms that have not lost their force but are outdated in content. The fourth classification is based on subjects and includes historical official interpretation and historical unofficial interpretation.Conclusions. Correct approach to the concept and process of historical interpretation of the content of legal norms, as well as the choice of the type of historical interpretation helps in law enforcement, allows you to put forward scientific hypotheses, predict the further development of law based on historical knowledge of the interpreted norm, assess the possibility of reviving canceled acts in recurring socio-economic and political-legal situations.